Roman law before the Twelve Tables : an interdisciplinary approach - Bell, Sinclair; Plessis, Paul J. du (Edinburgh : Edinburgh University Press, 2020)
Bringing together a team of international experts from different subject areas - including law, history, archaeology and anthropology - this text re-evaluates the traditional narratives surrounding the origins of Roman law before the enactment of the Twelve Tables.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 5, 2020).
Keywords: Roman law -- History; Law; Jurisprudence & general issues